Rethinking childhood: zbornik radova s međunarodne znanstveno-umjetničke konferencije održane u Zadru 4. i 5. lipnja 2021. (Morepress Books, 2025)
The Department of Teacher and Preschool Teacher Education (University of Zadar) has held a virtual conference on 4-5 June 2021 under the name Rethinking Childhood (cro. Nova promišljanja o djetinjstvu). The co-organizers of the conference were the Department of Teacher Studies in Gospić, the Faculty of Education of the University of Maribor and the Croatian Association of Researches in Children’s Literature. Upon organising the event, the Program Committee was influenced by contemporary scientific postulates resulting from the interdisciplinary dialogue between different scientific fields. In order to find a more complete approach to a rather specific scientific problem, the conference was conceived as a meeting place of different scientific, artistic and methodological perspectives when it comes to reflections on childhood.